Field notes contributed by John Van Dyk, fall 1993 - Van Dyk, John, 1936-et al (1993)
Fall report of birds found in northwest Iowa contributed by John Van Dyk. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1993. Plustek - flatbed